Low temperature synthesis and photocatalytic performance of tungsten trioxide film. (January 2016) - Zhu, Y. F.; Yu, C. F.; Ni, C. Y.
Abstract : The synthesis of three-dimensional tungsten trioxide hydrate (WO3 .H2 O) films assembled by two-dimensional nanosheets has been realised through a seed assisted process at low temperature. The morphology of the film was observed with a field emission scanning electron microscope. The results indicate that the morphology of the film can be controlled by changing the concentration of chemicals used in the deposition process and the reaction time. Based on the experimental observations, a formation mechanism has been proposed. X-ray diffraction study indicates that these films have orthorhombic structure and are well crystallised. After heat treatment, the films transform to monoclinic WO3 . In order to investigate the photocatalytic activity, the WO3 films were coated with stearic acid (SA), and their water contact angle was found to be 64° after coating. With the decomposition of SA molecules, the WO3 film switched to their initial hydrophilic state, accompanied by a reversible change of the film colour.